Estudo da Adição do Promotor Cu aos Catalisadores Pt/Al2O3 e Pt/Nb2O5 para a Oxidação Seletiva de CO - Mozer, Thiago Simonato (2005)
The fuel cells are an alternative to generate energy without polluting the environment. They produce electric energy through the reaction of hydrogen with the oxygen from air. The product of the reaction is water. It is an interesting form of generation energy because it s a clean technology. The hydrogen used as combustible for the fuel cells is proceeding from the steam reform hydrocarbons, this hydrogen contains about 1% of carbon monoxide. The hydrogen, used as combustible for the polymer electrolytic membrane fuel cell (PEMFC), can not contain more than 10 ppm of carbon monoxide. The presence of carbon monoxide in concentrations above 10 ppm poisons the anode of Pt of the cell. In this work it was studied catalyst that can be used to oxidize carbon monoxide selectively in the presence of hydrogen. The catalysts studied for the selective oxidation of CO had been: 1%Pt/Al2O3, 1%Pt-1%Cu/Al2O3, 1%Pt/Nb2O5, 1%Pt-1%Cu/Nb2O5, 1%Cu/Al2O3, 1%Cu/Nb2O5, Al2O3 and Nb2O5. The catalysts supported on Nb2O5 had better selectivity in relation to the catalysts supported in Al2O3 due to the strong metal-support interaction effect (SMSI) that occurs in the catalysts supported in Nb2O5. The addition of the Cu promoted the reaction, increasing the selectivity for the oxidation of the CO due to the interaction of the Pt with the Cu. The Pt based catalysts had 100% of CO conversion to CO2 around 100ºC. Better results had been gotten when the catalysts were reduced at 300ºC, the selectivity of the catalysts was lesser when reduced at 500ºC. The selectivity was 47% for the Pt/Al2O3 catalyst, 58% for the PtCu/Al2O3 catalyst and 54% for the Pt/Nb2O5 catalyst. The PtCu/Nb2O5 catalyst reduced at 300ºC presented the best selectivity among the tested catalysts, around 64%, as much for the bimetallic interaction of platinum with copper how much for the interaction of the active phase with the support. The oxides Al2O3 and Nb2O5 had presented 100% of CO conversion even though the ignition temperature had been lesser in relation to the Pt based catalysts, the Al2O3 presented 25% of selectivity while that the Nb2O5 presented 49% of selectivity. The Cu/Al2O3 catalyst did not present activity for the selective oxidation of CO already the Cu/Nb2O5 catalyst, when activated 300ºC, it presented 100% of CO conversion around 230ºC with 40% of selectivity.